Education And Maternal Self-Confidence In Caring For Premature Babies - Permatasari, Indah; Herlina, Herlina Herlina (LPPM Universitas Prima Nusantara Bukittinggi, 2024)
Background: The high number of preterm births in 2014-2015, Indonesia is one of the countries that contributes the highest premature rate of 19% and is a major factor in perinatal mortality. RSAB Harapan Kita West Jakarta has a rate of 3.46% about 105 mothers who gave birth to premature babies within 3 months. The formulation of this problem is the health of premature babies who need intensive and special care so that most of them can affect the self-confidence of the baby's parents.Purpose: The purpose of this study was to determine whether there is a relationship between maternal education and maternal confidence in caring for premature babies at RSAB Harapan Kita, West JakartaMethods: This study used quantitative methods and used a cross sectional approach with 38 samples obtained by non-probability sampling method and total sampling technique.Results: The results showed that there was no significant relationship between maternal education and maternal confidence in caring for premature babies with a p-value of 0.721 (? 0.05).Conclusion: There are other factors apart by education that may affect mothers' confidence in caring for premature babies such as health education. Thus, the researcher suggests the future researchers to examine the effect of health education on the confidence of mothers in taking care of premature babies.